2010
DOI: 10.1016/j.jcta.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

On cycle systems with specified weak chromatic number

Abstract: A weak k-colouring of an m-cycle system is a colouring of the vertices of the system with k colours in such a way that no cycle of the system has all of its vertices receive the same colour. An m-cycle system is said to be weakly k-chromatic if it has a weak k-colouring but no weak (k − 1)-colouring. In this paper we show that for all k 2 and m 3 with (k, m) = (2, 3) there is a weakly k-chromatic m-cycle system of order v for all sufficiently large admissible v.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The reason for these particular congruence conditions will become apparent when we employ these examples in Section 5 to establish the asymptotic existence of c-chromatic BIBDs for each c ≥ 2. Our approach in this section is inspired by a technique used in [4], and also bears similarities to methods used in [12]. Before proving Lemma 4.4, we require three preliminary lemmas.…”
Section: Examples Of C-chromatic Bibdsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for these particular congruence conditions will become apparent when we employ these examples in Section 5 to establish the asymptotic existence of c-chromatic BIBDs for each c ≥ 2. Our approach in this section is inspired by a technique used in [4], and also bears similarities to methods used in [12]. Before proving Lemma 4.4, we require three preliminary lemmas.…”
Section: Examples Of C-chromatic Bibdsmentioning
confidence: 99%
“…G, B) is a transversal design with group size 13 and block size 4. Let S 1 = {(0, 1), (0, 2), (0, 3), (0, 4), (1, 1), (1,2), (1,3), (1,4), (2, 1), (2, 2), (2, 3), (2,4), (3,1), (3,2), (3,8), (3,9)}; S 2 = {(0, 5), (0, 6), (0, 7), (0, 8), (1,5), (1,6), (1,7), (1,10), (2,7), (2,8), (2,9), (2,12), (3, 0), (3,3), (3,10), (3,11)}; S 3 = {(0, 0), (0, 9), (0, 10), (0, 11), (1, 0), (1,8), (1,11), (1,12), (2, 0), (2,5), (2,6),…”
Section: Examples Of C-chromatic Bibdsmentioning
confidence: 99%
See 2 more Smart Citations
“…An m-cycle system of order n > 1 is a partition of the edges of the complete graph K n into m-cycles. Also, Horsley and Pike [5] showed that for all k 2 ⩾ and m 3 ⩾ with k m ( , ) (2,3) ≠ , there exist k-chromatic m-cycle systems of all admissible orders greater than or equal to some integer n k m , . A bipartite graph G m n , is a graph whose vertex set can be partitioned into two subsets V 1 and V 2 with m and n vertices each, such that every edge of G m n , has one vertex in V 1 and one vertex in V 2 .…”
Section: Introductionmentioning
confidence: 99%